Model Prediksi Kepemilikan Manajerial Perusahaan Go Public Berbasis Pendekatan Multinomial Logit - Suteja, Jaja (Jurnal Trikonomika, 2011)
The objective of this research is to provide empirical evidence of the factors that influence the probability of the managers to take part in managerial ownership. The examined factors on this study are consisted of investment opportunity sets, leverage, dividend payout ratio, profitability, growth rate of the firm, size of the firm, value of the firm, equity market value, and institutional ownership. The sample is consisted of 66 firms of which 41 of them had no managerial ownership, 10 firms had medium managerial ownership and 15 firms had high managerial ownership. The data collected is the data in the year 2007 and it is conducted by stratified random sampling. Multinomial Logit Regression is used in order to test the research hypothesis. The research finding indicates that investment opportunity sets, equity market value, size of the firm and institutional ownership are variables that significantly predict the managerial ownership. The result of this research also indicates that investment opportunity set, equity market value, the size of the firm as well as institutional ownership are statistically significant in predicting companies that have no managerial ownership.